Adolescent Mental Health Following Exposure to Positive and Harsh Parenting in Childhood. (June 2020) - Kingsbury, Mila; Sucha, Ewa; Manion, Ian; Gilman, Stephen E.; Colman, Ian
Objectives: The purpose of the present study was to assess longitudinal associations between positive and harsh parenting in childhood and adolescent mental and behavioral difficulties. Methods: Data were drawn from Canada's population-based National Longitudinal Survey of Children and Youth (data collected from 1994 to 2009, analyzed 2018). The sample included 9, 882 adolescents aged 12/13 years old. Parents self-reported positive and harsh parenting when children were 6/7, 8/9, and 10/11 years old. Symptoms of depression/anxiety, hyperactivity, physical aggression, social aggression, and suicidal ideation were self-reported by adolescents at age 12/13. Linear regression was used to examine the associations between parenting behaviors at each age and adolescent psychiatric symptoms, adjusted for children's baseline symptoms. Results: Harsh parenting at 10/11 was associated with elevated symptoms of early-adolescent physical aggression, social aggression, and suicidal ideation for boys only, and for all children at earlier ages. Beginning at age 8/9, harsh discipline was associated with elevated symptoms of depression/anxiety for boys only. Overall, positive parenting at age 6/7 was protective against depression/anxiety, physical aggression, and social aggression. Significant sex differences emerged beginning at age 8/9, with positive parenting associated with higher symptoms of depression/anxiety for boys only. Positive parenting at age 10/11 was associated with increased depression/anxiety, physical aggression, social aggression, and suicidal ideation among boys, but decreased symptoms of physical aggression, social aggression, and suicidal ideation among girls. Conclusions: Results suggest that the impact of positive and harsh parenting may depend on age and sex, with harsh parenting being more detrimental to boys as they approach adolescence.